2021
DOI: 10.3389/fped.2021.793446
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine Reference Limits in Pediatric Population—A Single Center Electronic Health Record-Based Database in Taiwan

Abstract: Objective: To assess age- and sex-specific serum creatinine levels in a pediatric population using a hospital-based database in Taiwan.Study Design: Data on serum creatinine levels were obtained from the National Taiwan University Hospital-integrated Medical Database (NTUH-iMD). Due to the possibility of having acute kidney injury or chronic kidney disease, individuals with multiple serum creatinine measurements were excluded, and outliers in each age- and sex-specific group were also subsequently removed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Similarly, the Hg and urea-creatinine elevations detected in the older age group were also attributed to the increase in physiological Hg with age, independent of HRV/EV infection, and the gradual increase in serum creatinine level WAS due to the increase in muscle mass with age. 30,31 In the cases, 65.3% received COT, 33.3% received NIV, 32% received HFNC-OT and 16% received IMV support. The high rate of COT may be attributed to its role as both a primary treatment modality and a transitional method among other support techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the Hg and urea-creatinine elevations detected in the older age group were also attributed to the increase in physiological Hg with age, independent of HRV/EV infection, and the gradual increase in serum creatinine level WAS due to the increase in muscle mass with age. 30,31 In the cases, 65.3% received COT, 33.3% received NIV, 32% received HFNC-OT and 16% received IMV support. The high rate of COT may be attributed to its role as both a primary treatment modality and a transitional method among other support techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the Hg and urea-creatinine elevations detected in the older age group were also attributed to the increase in physiological Hg with age, independent of HRV/EV infection, and the gradual increase in serum creatinine level WAS due to the increase in muscle mass with age. 30,31…”
Section: Discussionmentioning
confidence: 99%
“…In the study that we conducted, serum creatinine was higher in infected patients with vitamin D levels above the threshold value. Children's normal values for creatinine are highly age-dependent and influenced by sex, especially in adolescence when the muscle mass grows rapidly for males [95,96]. In a cohort study on over 1200 participants in Spain, González-Molero et al demonstrated that 25-hydroxyvitamin D levels were correlated with creatinine in the normal population [97].…”
Section: Discussionmentioning
confidence: 99%
“…SCr is typically regarded as the “gold standard” biomarker for clinically diagnosing AKI. However, there are two drawbacks when using SCr as a biomarker in infancy: first, muscle mass, which varies between preterm and term neonates, significantly influences SCr levels [ 15 ] and second, during the first 1–2 weeks after birth, the SCr levels of neonates primarily reflect their mother’s SCr [ 7 ]. Typically, neonatal SCr levels stabilize within a few days or weeks [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAKI is defined as AKI persisting > 7 days. Recovery from AKI is defined as one of the following: SCr level dropped to baseline at infancy or the initial level [ 15 ]; UO amount ≥ 0.5 mL/kg/h over 6 consecutive hours [ 6 , 16 ]; and RRT discontinued or no longer needed.…”
Section: Methodsmentioning
confidence: 99%